From A Real Economy to A Green Economy: Is Such a Transition Possible and What Should It Be? - S. Bobushev , Temirbek (International Journal of Scientific Research and Management (IJSRM), 2023)
It is no secret that one of the popular terms that is widely used in the public press is the term green economy. However, all we hear about this are opinions, the truth lies in actions. The fact is that we know quite a lot about the content of a real economy and even a green economy, but we practically do not know how to make the transition from one system to another. All statements about the significance and manifestations of the green economy, in most cases, represent the expected or possible consequences of the transition from a real economy to a green economy. However, unfortunately, researchers and, more often than not, politicians and publicists forget that the problem of using the green economy model is not only to move to possible reductions in emissions through the use of “clean” energy in industrial production, transport, etc., but that energy production is still largely provided by hydrocarbon sources. The share of the latter is still high in most countries of the world, and compared to alternative energy sources, such energy production is assessed as more efficient.